2013
DOI: 10.1002/gps.4006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of factors that influence physician decision making regarding medication use in patients with dementia at the end of life

Abstract: Further research is required into other factors that may impact upon physicians' prescribing decisions for these vulnerable patients and to clarify how the factors examined in this study influence prescribing decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 76 publications
1
38
1
1
Order By: Relevance
“…The present findings regarding possible correlates of opinions of whether AH, AT and AN should be administered or not when a patient's life expectancy falls warrant a few comments. These practices are widely used, even in cases with a limited residual life expectancy, even though the benefits are not apparent from the literature . It might be that healthcare providers working in geriatrics tend to administer AT and AN less to patients with a life expectancy limited to a few weeks, because they know more about terminal dementia conditions and the process of dying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings regarding possible correlates of opinions of whether AH, AT and AN should be administered or not when a patient's life expectancy falls warrant a few comments. These practices are widely used, even in cases with a limited residual life expectancy, even though the benefits are not apparent from the literature . It might be that healthcare providers working in geriatrics tend to administer AT and AN less to patients with a life expectancy limited to a few weeks, because they know more about terminal dementia conditions and the process of dying.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that AN creates more ethical dilemmas in clinical management of end life than AH or AT. It remains to be explored whether this option is as a result of a non‐explicit, but wanted, intervention to hasten death, or if this attitude is instead related to the probability that AN leads to more adverse effects …”
Section: Discussionmentioning
confidence: 99%
“…The question of when to discontinue ChEI therapy remains challenging given the lack of general consensus among clinicians [54,55]. ChEIs are frequently prescribed in nursing home residents and at the time of hospice enrollment, with one cross-sectional study of 5406 nursing home residents with advanced dementia finding that ChEIs were the most commonly prescribed drug (36.4 % of patients) [56][57][58].…”
Section: Cholinesterase Inhibitors At the End Of Lifementioning
confidence: 99%
“…Furthermore, there were some medications, namely expectorants and tricyclic antidepressants, for which classifications of appropriateness varied widely. This variation may in part be explained by cross-national or cultural differences in prescribing in US and UK jurisdictions but may also reflect the complexity and variability in decision-making regarding medication use at the end of life for patients with advanced dementia and the lack of evidence-based guidance available to guide clinical practice [8,27,41].…”
Section: Discussionmentioning
confidence: 99%